Resonant photoluminescence studies of carrier localisation in c-plane InGaN/GaN quantum well structures. (9th April 2018) - Blenkhorn, W E; Schulz, S; Tanner, D S P; Oliver, R A; Kappers, M J; Humphreys, C J; Dawson, P
Abstract: In this paper we report on changes in the form of the low temperature (12 K) photoluminescence spectra of an InGaN/GaN quantum well structure as a function of excitation photon energy. As the photon energy is progressively reduced we observe at a critical energy a change in the form of the spectra from one which is determined by the occupation of the complete distribution of hole localisation centres to one which is determined by the resonant excitation of specific localisation sites. This change is governed by an effective mobility edge whereby the photo-excited holes remain localised at their initial energy and are prevented from scattering to other localisation sites. This assignment is confirmed by the results of atomistic tight binding calculations which show that the wave function overlap of the lowest lying localised holes with other hole states is low compared with the overlap of higher lying hole states with other higher lying hole states.